2010
DOI: 10.2165/11204340-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram

Abstract: Escitalopram is a selective serotonin reuptake inhibitor (SSRI), and is the second antidepressant to be approved for use in treating major depressive disorder (MDD) in adolescent patients (aged 12-17 years) in the US. In a randomized, double-blind, flexible-dose, multicenter trial, once-daily escitalopram 10-20 mg (n = 154) for 8 weeks was significantly better than placebo (n = 157) in improving the severity of depressive symptoms (as assessed by the change in the Children's Depression Rating Scale-Revised [CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…After the warning, SSRI treatment in children declined, yet suicide rates remained the same, and no alternative drug has filled the void left by SSRIs for children with psychiatric disorders (Katz et al, 2008). A new clinical trial of the S-enantiomer citalopram, which is the second SSRI (following fluoxetine) approved by the FDA for treatment of depression in children, indicated that it did not differ from placebo in the number of suicides attempted (Yang and Scott, 2010). Together, these results suggest that suicidality may not be related to SSRI treatment per se, but a risk associated with the disease itself.…”
Section: Abnormal Sert Development and Diseasementioning
confidence: 99%
“…After the warning, SSRI treatment in children declined, yet suicide rates remained the same, and no alternative drug has filled the void left by SSRIs for children with psychiatric disorders (Katz et al, 2008). A new clinical trial of the S-enantiomer citalopram, which is the second SSRI (following fluoxetine) approved by the FDA for treatment of depression in children, indicated that it did not differ from placebo in the number of suicides attempted (Yang and Scott, 2010). Together, these results suggest that suicidality may not be related to SSRI treatment per se, but a risk associated with the disease itself.…”
Section: Abnormal Sert Development and Diseasementioning
confidence: 99%